Analysis of The Economic Impacts of Special Event: The Case of Jember Fashion Carnival in Jember City - Christina L., Rudatin; Fauzi Mubarak (Journal of Business on Hospitality and Tourism, 2015)
This study investigated the economic impact a special event in the tourism industry. Jember Fashion Carnival 2015 became the object observed to conduct this study. Jember Fashion Carnival is an annual event from Jember City, but until this time not anyone makes observations to investigate the economic impact of outside tourist that come to Jember City during the time of the event. This study used a semi-structured, self-administered questioner was employed in collecting relevant social and economic data from respondents. A convenience sample of 100 attendees was used to determine the economic impact generated. The Respondents is the tourists who come from outside the city of Jember and attend the Jember Fashion Carnival 2015. The Economic impact assessment based on the amount of spending money from the attendees, with the details information some expenditure categories such as; accommodation, food, entertainment, souvenirs, communication and other types of expenditure. The result supported the claim that the event of Jember Fashion Carnival 2015 has positive economic impact on the host community.